Constructive description of monogenic functions in a finite-dimensional semisimple commutative algebra - Plaksa, S.A.; Pukhtaievych, R.P. (Reports of the National Academy of Sciences of Ukraine, 2014)
We obtain a constructive description of monogenic functions taking values in a finite-dimensional semisimple commutative algebra by means of analytic functions of the complex variable. We prove that the mentioned monogenic functions have the Gateaux derivatives of all orders.